Evaluation of antimicrobial activity of Malus domestica fruit extract from Kashan area - Sara Jelodarian; Abdolrasoul Haghir Ebrahimabadi; Fereshteh Jookar Kashi (Mashhad University of Medical Sciences, 2012)
Objective: Many species of plants present noticeable potency against human bacterial and fungal pathogens. Materials and Methods: In the current study, antimicrobial activity of the fresh fruits of 4 cultivars (A to D) of Malus domestica cultivated in the Qamsar area of Kashan, Iranwas investigated. The disk diffusion and minimal inhibitory concentration (MIC) evaluation antimicrobial activity tests were performed. Results: The samples showed moderate antimicrobial activities with inhibition zones from 11 to 16 mm in these tests. Cultivar D with inhibition zones of 16, 14, and 12 mm for E. coli, S. epidermidis and K. pneumoniae, respectively exhibited the best results in these tests. Cultivar A also showed a zone of inhibition of 11 mm against P. aerouginosa. Conclusion: Moderate antimicrobial activities were observed for the studied apple cultivars.